A Study of Hadiths About Riya' in the Book of Hidayatus Salikin Perspective of Abdul Samad Al-Falimbani - Aini, Mufidatun Nur; Halim, Nuruddin Ghilman; Muhid, M; Muthoharoh, Isnaini Luluatim (Universitas Muhammadiyah Surakarta, 2024)
The Qur'an and hadith are the main guides for Muslims, but the temptation of lust sometimes leads humans to riya' behavior, which is doing good only for the praise of humans, not the pleasure of Allah. The book